2013
DOI: 10.1103/physrevlett.110.151105
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the AtmosphericνeFlux in IceCube

Abstract: We report the first measurement of the atmospheric electron neutrino flux in the energy range between approximately 80 GeV and 6 TeV, using data recorded during the first year of operation of IceCube's DeepCore low-energy extension. Techniques to identify neutrinos interacting within the DeepCore volume and veto muons originating outside the detector are demonstrated. A sample of 1029 events is observed in 281 days of data, of which 496±66(stat)±88(syst) are estimated to be cascade events, including both elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 29 publications
10
139
0
3
Order By: Relevance
“…After a few years of operation, statistics have been accumulated and a number of studies of atmospheric neutrinos have been performed. Atmospheric neutrino flux measurements have been carried out in a wide range of energies [112][113][114][115][116][117], low-energy atmospheric neutrino data have been considered to constrain neutrino oscillation parameters to levels comparable to other neutrino oscillation experiments [51,52], low-energy data have also been used to set constraints on matter NSI [49], and light sterile neutrinos, claimed as possible explanations of short baseline Figure 8. Posterior (68% and 95%) probability contours for two 10-year forecasts of high-energy atmospheric neutrino data in IceCube.…”
Section: Discussionmentioning
confidence: 99%
“…After a few years of operation, statistics have been accumulated and a number of studies of atmospheric neutrinos have been performed. Atmospheric neutrino flux measurements have been carried out in a wide range of energies [112][113][114][115][116][117], low-energy atmospheric neutrino data have been considered to constrain neutrino oscillation parameters to levels comparable to other neutrino oscillation experiments [51,52], low-energy data have also been used to set constraints on matter NSI [49], and light sterile neutrinos, claimed as possible explanations of short baseline Figure 8. Posterior (68% and 95%) probability contours for two 10-year forecasts of high-energy atmospheric neutrino data in IceCube.…”
Section: Discussionmentioning
confidence: 99%
“…The ν μ and ν e atmospheric neutrinos have been reported by IceCube [29,30]. The electronic neutrino background has limited data with important uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the data were collected with an exposition time of t ν μ exp ¼ 359 days and t ν e exp ¼ 281 days for the muon and electron neutrinos, respectively [29,30]. We have found that for DM annihilating into the W þ W − boson channel, we need a resolution angle 0.18°≲ θ ≲ 0.72°and low-energy cutoff 818 GeV ≲ E ν min ≲ 1811 GeV to get a signal between 5σ and 2σ with a minimum of 2 years of exposition time and a maximum of 5 years for an effective detector area of 50 m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the source, the angular distribution of events is considered consistent with an isotropic arrival direction of neutrinos (Aartsen et al 2013c(Aartsen et al , 2014a and the majority of events detected by IceCube are believed to be from cosmological distances or, less likely, from the Galactic halo. In a recent update, Aartsen et al (2014b) have found no evidence of neutrino emission from discrete or extended sources in four years of IceCube data.…”
Section: Introductionmentioning
confidence: 99%